Pain in Parkinson's Disease Associated with COMT Gene Polymorphisms - Wanjun Li; Yongqian Chen; Bowen Yin; Limei Zhang (Behavioural Neurology)
Background. PD patients present high incidence of pain with unknown pathogenesis. Objective. We investigated the relation of COMT polymorphisms rs4633 and rs6267 with PD pain. Subjects and Methods. One hundred PD patients and 105 controls were evaluated with simplified Mc GILL pain scale and VAS scale. PD patients were assessed with H&Y grade, UPDRS score, and HAMD scale. Polymorphisms rs4633 and rs6267 were detected by PCR and direct sequencing. Results. Fifty-seven percent of PD patients experienced pain, consisting of PD-related pain (64.91%) (the majority was dystonia pain) and non-PD-related pain (35.09%) (psychogenic pain was most frequent). The frequency of rs6267 genotype “GT/TT” and allele “T” was higher in PD pain. No difference was observed in frequencies of rs4633 between PD pain and without pain. UPDRS and depression score were higher in PD pain. The onset age was earlier in PD-related pain (57.43 ± 19.71) than non-PD-related pain (63.36 ± 6.88). Conclusion. PD patients possess a high prevalence of pain. Dystonia pain was the most frequent type of PD-related pain. COMT gene rs6267 allele “T” associated with PD pain. PD pain was influenced by disease severity and depression. PD onsets earlier in patients with PD-related pain than non-PD-related pain.